2015
DOI: 10.3803/enm.2015.30.3.395
|View full text |Cite|
|
Sign up to set email alerts
|

Acromegaly with Normal Insulin-Like Growth Factor-1 Levels and Congestive Heart Failure as the First Clinical Manifestation

Abstract: The leading cause of morbidity and mortality in patients with acromegaly is cardiovascular complications. Myocardial exposure to excessive growth hormone can cause ventricular hypertrophy, hypertension, arrhythmia, and diastolic dysfunction. However, congestive heart failure as a result of systolic dysfunction is observed only rarely in patients with acromegaly. Most cases of acromegaly exhibit high levels of serum insulin-like growth factor-1 (IGF-1). Acromegaly with normal IGF-1 levels is rare and difficult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…In this study, normal IGF-1 level was not observed in any of the patients. This may be due to majority of the patients in our study presented with macroadenoma on the contrary to the case reports in the literature [17][18][19][20].…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In this study, normal IGF-1 level was not observed in any of the patients. This may be due to majority of the patients in our study presented with macroadenoma on the contrary to the case reports in the literature [17][18][19][20].…”
Section: Discussioncontrasting
confidence: 87%
“…However, to the best of our knowledge this is the first comparative study investigating impact of hepatic insulin resistance on IGF-1 levels in patients with acromegaly. Only low or normal IGF-1 levels are reported in patients with acromegaly with unregulated type 2 DM as case reports [17][18][19][20]. Increase in IGF-1 levels are reported with the improvement of glycemic regulation in these patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A number of factors have been evaluated in order to assess the risk of hypopituitarism after GKRS. The studies published so far showed that the prescription dose of radiation and the tumor volume size are major risk factors for new pituitary hormone insufficiency [25,26]. It was shown that the 5-year risk of developing new pituitary deficits was higher for tumors with a volume higher than 4 cm 3 (58% vs 18%) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Median patients' age was 56 years . GKRS was performed using the Leksell gamma knife Model C. The median prescription radiation dose was 20 Gy (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and the median tumor volume size was 3.4 cm 3 (0.06-16.81). New onset hypopituitarism was defined as a new deficit of one of the three hormonal axes (corticotroph, thyreotroph or gonadotroph) ≥3 months following GKRS.…”
mentioning
confidence: 99%